Acceptable load carriage for primary school girls - Razali, R.; Abu Osman, Noor Azuan; Shasmin, H.N.; Usman, J.; Wan Abas, Wan Abu Bakar (2005)
Randomized six primary school girls aged between 9 to 10 years old completed this study at the Motion Analysis Laboratory, Department of Biomedical Engineering, University of Malaya, Malaysia. Three different loads were used (10, 15 and 20 of their body weight) and 0 was used as control during level walking. The data obtained, both kinetics and kinematics, were analyzed using the Peak MotusÂ® 7.2.4 software from PEAK Performance TechnologiesÂ® and SPSSÃ version 12.0 software. The results indicated that the peak ground reaction forces increased with increasing backpack loads. The hip and knee flexion/extension increased as the loads increased. The stride length and walking speed decreased, while the cadence showed no significant difference (P>0.05). If the trunk angle is taken as the criterion to determine acceptable backpack loads for children, these loads should not exceed 10 of the childrenâs body weight.